Ultra-high pressure treatment improve the content of characteristic aromatic components of melon juice from the view of physical changes - Liu, Xiao; Liang, Feng; Wang, Bing Su; Ren, Fei Yue; Wang, Wei; Zhang, Chao (Frontiers in Nutrition, 2024)
The effectiveness of ultra-high pressure (UHP) technology in retaining the flavor of fresh fruit and vegetable juices has been acknowledged in recent years. Along with previously hypothesized conclusions, the improvement in melon juice flavor may be linked to the reduction of its surface tension through UHP. In this paper, the particle size, free-water percentage, and related thermodynamic parameters of melon juice were evaluated in a physical point for a deeper insight.The results showed that the UHP treatment of P2-2 (200 MPa for 20 min) raised the free water percentage by 7,000 times than the other treatments and both the melting enthalpy, binding constant and Gibbs free energy of P2-2 were minimized. This significantly increased the volatility of characteristic aromatic compounds in melon juice, resulting in a 1.2-5 times increase in the content of aromatic compounds in the gas phase of the P2-2 group compared to fresh melon juice.